Case study : Mr. DIY / Muhamad Farhan Mohd Razali - Mohd Razali, Muhamad Farhan (2021)
This business is based on entrepreneurship and research of Tan Yu Yeh or known as Mr. DIY. He is the Executive Vice Chairman and Non-independent Executive Director. Tan Yu Yeh can we put him as role model in business because he brings a great brush is not easy to give up and keep moving forward and brings his business MR. DIY to another level of achievement and being a stable store. In this research studies, I want to peel about success business man and a few things that we need to know behind the success of a business man and his company. The pain and the hardships that has to been faced by Tan Yu Yeh before the success and become the billionaire.